THE ROLE OF A PAUSE IN THE INTERPRETATION OF CHARACTER SUBTEXTS IN A. BARICCO'S NOVEL "OCEAN SEA" - Rasulova Munira (Journals Park Publishing, 2022)
This article discusses the pause as a communicatively significant component of dialogic fragments, as well as its role in the interpretation of character subtexts in the works of A. Baricco. By interpreting the reasons for silence, one can obtain important additional information about the characters and reveal their emotional and psychological state. The material of the study is A. Baricco's novel "Ocean Sea".
Keywords: text; interpretation; pause